Factors influencing distribution network structural decisions and distribution management policies in the food distribution industry - mahdi Haghighi; zohre dehdashtishahrokh; vahid khashei; Reza hajari (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2020)
This study is conducted to identify and analyze the relationship between the factors affecting the distribution network design (DND) in the food distribution industry in Iran. In this paper, for the first time, the distribution network design has been classified into two main areas of the strategic structure of the distribution network and the distribution management policies and the impact of the key variables on distribution network design has been investigated. This study is descriptive, exploratory and using quantitative research method. The statistical population of this research is all 54 food distribution companies in Iran. Using a census method, a questionnaire was sent to all general and marketing managers of these companies (108 people). 92 questionnaires were completed, according to the established criteria, only 81 questionnaires could be used, which also covers the standards of Cochran formula. The partial least squares (PLS) method is used to analyze the data and the results indicate that product characteristics, service requirements, demand characteristics, supply characteristics, and economic variables are the key variables that affect the distribution network design. Given the lack of research on the distribution network design and the study of the factors affecting the formation of strategic distribution structures and policies, it can be argued that this article provides valuable insights for academics and professionals, because in the very study the various components of distribution network design, the decisions related to the design of the distribution network and the analysis of the main factors affecting the distribution network structure are presented.